Performance evaluation of 2-dimentional anthropometry method in measurement of hand dimentions - SH Soury; E Habibi; A Hasanzade (طب کار)
Introduction: Various studies carried out on different photo anthropometry, but each one had some deficiencies which during the years they have been resolved. In the current study in order to determine the anthropometric dimensions of the hand, two-dimensional images were used. And its results were compared with manual methods (caliper). The objective of this paper is to test the efficiency of 2D (Two-dimensional) image processing software in Photo anthropometry of hand. Methods: In this applied research, 204 workers were selected.7 dimension of their hand was measured. The taken photos were analyzed by Digimizer software, version 4.1.1.0. And Digital Caliper (Model: Mitutoyo Corp, Tokyo, Japan) was used via manual method. Results: t-test statistical test on data revealed that there is no significant difference between the manual and photo anthropometric results (p>0.05), and the correlation coefficients for hand dimensions are similar in both methods illustrated in the range of 0.9-0.95. Conclusion: The statistical analyses showed that photo anthropometry can be replaced with manual methods. Also it can provide a great help to develop an anthropometric database for work gloves manufacturers. Since the hand anthropometry is a necessary input for tool design, this survey can be used to determine the percentiles of workers' hands